Pancreatic metastasis from squamous cell lung cancer: computed tomography and magnetic resonance imaging findings. Issue 2 (February 2021) - Lu, Tao; Li, Xinglan; Zhou, Yao
Metastatic lesions of the pancreas are uncommon. The incidence of pancreatic involvement with squamous cell carcinoma is the lowest among the different histological subtypes of lung cancer. We present the clinical data, pathological findings, and imaging features of two cases of pancreatic metastasis from squamous cell lung cancer with a literature review. A 75-year-old man and a 67-year-old man were both diagnosed with metastatic pancreatic tumors from squamous cell lung cancer during a multidisciplinary team discussion. Both patients were misdiagnosed as having a neuroendocrine tumor of the pancreas by imaging examination before surgery. Squamous cell lung cancer metastasis to the pancreas is extremely rare, and the atypical clinical and radiological presentations make it difficult to distinguish metastatic tumors from primary pancreatic tumors.